The publicness and sociabilities of the ottoman coffeehouse - Kömeçoglu, Ugur (Javnost (Ljubljana), 2005)
It has been emphasised that in the Ottoman society there was no public sphere in its .political. sense, at least until the nineteenth century. The importance of a cultural interpretation of this sphere has been ignored by sociologists, too. Sociological studies of the old urban publicness were restricted to historians. analysis, and a culturalistic view of sociology has been lacking. In this article I discuss this issue by focusing on the publicness created by the Ottoman coffeehouses. The public sphere that emergedwas of course not similar to the rational and rather elitist understanding of the concept. The coffeehouses, which were part of the Ottomanpublic sphere, represented the complex everyday realities of that public life, the political and cultural contest and negotiations within the Ottoman society.
Keywords: Turčija; Turkey; javna sfera; javnost; komuniciranje; communication; javno mnenje; sociologija kulture